2019
DOI: 10.3168/jds.2018-15839
|View full text |Cite
|
Sign up to set email alerts
|

Effect of teatcup removal settings on milking efficiency and milk quality in a pasture-based automatic milking system

Abstract: In automatic milking systems (AMS), it is important to maximize the amount of milk harvested per day to increase profitability. One strategy to achieve this goal is to reduce the time it takes to milk each cow. Several studies in conventional milking systems have shown that milking time can be reduced by increasing the milk flow rate at which the teatcup is removed. One study analyzed the effect of increasing the milk flow switch point on milking time in a confinement AMS. No research has been conducted on tea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…However, as practice shows [8,9], the main issue related to executing the process of extracting milk from the udder is the negative effect of milking machines on the mammary gland of the animal. In this regard, there is a question about the possibility and necessity of milk production at dairy farms, the technical equipment of which is one of the most important tasks.…”
Section: Introductionmentioning
confidence: 99%
“…However, as practice shows [8,9], the main issue related to executing the process of extracting milk from the udder is the negative effect of milking machines on the mammary gland of the animal. In this regard, there is a question about the possibility and necessity of milk production at dairy farms, the technical equipment of which is one of the most important tasks.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Rasmussen (1993) documented improved teat tissue conditions in cows that were milked with an increased ACR setting. These initial studies were followed by work from researchers around the globe investigating different ACR settings in conventional milking systems (Stewart et al, 2002;Magliaro and Kensinger, 2005), pasture-based systems (Clarke et al, 2004;Jago et al, 2010;Burke and Jago, 2011;Edwards et al, 2013a,b), confinement (Ferneborg et al, 2016(Ferneborg et al, , 2019Krawczel et al, 2017), and pasture-based (Silva Boloña et al, 2019) automatic milking systems. The majority of these studies supported the results of the earlier works.…”
Section: Introductionmentioning
confidence: 99%
“…Considerable research effort has been spent exploring ways to improve milk harvesting efficiency, one of which is the choice of end-of-milking criteria for individual cows. The majority of the research into end-of-milking criteria has used milk flow rate (kg/min) to determine when automatic cluster removers (ACR) are activated (Rasmussen, 1993;Stewart et al, 2002;Magliaro and Kensinger, 2005;Burke and Jago, 2011;Edwards et al, 2013a;Edwards et al, 2013b;Silva Boloña et al, 2019), although some studies have used a time-based approach (Clarke et al, 2004;Jago et al, 2010a,b). Most research has concluded that these strategies can reduce cow milking duration without compromising milk yield or udder health, even for cows with a high SCC (Clarke et al, 2008).…”
Section: Introductionmentioning
confidence: 99%